Optical studies on a series of AlAs/GaAs short period superlattices - Oh, MS; Choi, SG; Kim, YD; Woo, DH; Koh, EH; Kim, SH; Kang, KN; Rhee, SJ; Woo, JC (KOREAN PHYSICAL SOC, 1999)
We present optical studies of a series of GaAs/AlAs short period superlattices (SLs) grown by Molecular Beam Epitaxy (MBE). The structural properties were examined by X-ray diffraction measurements. Quantum confinement of the electronic states was observed in the low temperature photoluminescence (PL). Spectroscopic ellipsometric (SE) measurements were also performed to determine energies of the interband transitions at room temperature. As n increases, we found that the lower transition energies (below 4.0 eV) decrease. The results are compared with low temperature photoluminescence measurements. We found a new structure at the lower E-2 peak, which demonstrates the best resolution of the E-2 structure in these SLs so far obtained by SE.
Keywords: GAAS/ALAS SUPERLATTICES; DIELECTRIC FUNCTION; SPECTROSCOPIC ELLIPSOMETRY; GAAS; TRANSITIONS; ALXGA1-XAS; SI; GE